World heritage, tourism, and identity : inscription and co-production - Bourdeau, Laurent; Barbas, Maria Gravari; Robinson, Mike (London, [England], UK : Routledge, Taylor & Francis Group, 2018)
The remarkable success of the 1972 UNESCO Convention Concerning the Protection of World Cultural and Natural Heritage is borne out by the fact that nearly 1,000 properties have now been designated as possessing Outstanding Universal Value and recognition given to the imperative for their protection. However, the remarkable success of the Convention is not without its challenges and a key issue for many Sites relates to the touristic legacies of inscription. For many sites inscription on the World Heritage List acts as a promotional device and the management challenge is one of protection, conservation and dealing with increased numbers of tourists. For other sites, designation has not brought anticipated expansion in tourist numbers and associated investments. What is clear is that tourism is now a central concern to the wide array of stakeholders involved with World Heritage Sites. It is a motivation for regions, states and communities to be put on the World Heritage List and it is certainly an outcome of being on the List. 0This volume, through a diverse range of international cases covering cultural, natural and mixed World Heritage Sites, covering both the developed and the developing world, examines the ways in which sites have been inscribed on the World Heritage List and what this has meant in terms of tourism relating to practical issues of management, carrying capacity and the experiences of tourists and local communities. It also looks at the way 'being on the list' shapes, and is shaped by, shifting values and politics at the macro and micro level.
World heritage and tourism: From opposition to co-production / Maria Gravari-Barbas, Laurent Bourdeau and Mike Robinson -- The use and impact of world heritage designation by Canadian Heritage Sites-An exploratory media analysis / Elizabeth A. Halpenny and Alexandra Arellano -- The impact of World Heritage on Tourism and the integrity of heritage: Some experience from Mexico / Richard Shieldhouse -- Implications of World Heritage designation for local residents: A case study from Taishan and Taiqian, China / Yixiao Xiang and Geoffrey Wall -- Cultural routes as world heritage sites: Challenges of the nomination of the ancient silk roads / Isabel Maria Torres Martinez -- The relationship between world heritage designation and local identity / Takamitsu Jimura -- Local consequences of global recognition: The "value" of world heritage status for Zanzibar Stone Town / Akbar Keshodkar -- Gender and (world) heritage: The myth of a gender neutral heritage / Sarah Ellen Shortliffe -- The local-to-global dynamics of world heritage interpretation / Noel B. Salazar -- Immediacy, photography and memory: The tourist experience of Machu Picchu / Sarah Quinlan Cutler, Sean Doherty and Barbara Carmichael -- The social life of the castles: Inclusion, exclusion, and heritage sites in Ghana / Ann Reed -- Place making and experience in world heritage cities / Luna Khirfan -- Le morne cultural landscape heritage site: Its different senses of attachment and contestation / Chaya Hurnath and Priscilla Sambadoo -- Expectations and experiences of visitors, at the giant's causeway world heritage site, northern Ireland / Kevin R. Crawford -- Demolition of tangible properties as an intangible practice / Ayako Fukushima -- The ethics of landscape: Discourses of cultural environmental sustainability in the heart of Neolithic Orkney World Heritage Site / Angela McClanahan -- Old maps, new traffics: Political itineraries around scattered heritage of Portuguese origin / Maria Cardeira da Silva -- World heritage and sustainable tourism: Shared values? / Jane Brantom.
Originally published: Abingdon, Oxfordshire : Ashgate, 2015.
Includes bibliographical references and index.
CBA
Text in English
Keywords: World Heritage areas; Heritage tourism